Chronic effects of superimposed electromyostimulation during cycling on aerobic and anaerobic capacity - Mathes, S.; Lehnen, N.; Link, T.; Bloch, W.; Mester, J.; Wahl, P. (European Journal of Applied Physiology, 2017)
Purpose: To examine if chronic endurance training by means of simultaneously applied, superimposed electromyostimulation (EMS) can be used to improve performance and physiological core parameters compared to the traditional cycling. Methods: Twenty-one male subjects (VO2peak 55.2 ± 5.1 ml/min/kg) were assigned to either a cycling (C) or cycling with superimposed EMS (C + E) group. Before and after the 4-week training period, including 14 sessions of moderate cycling [60 min at 60% peak power output (PPO)], participants performed a 20-min time-trial, a step test to exhaustion, a 30-s isokinetic sprint test, and maximum force- and power-tests. Markers of muscle damage and metabolic condition were assessed during the training period. Results: Step test results revealed increases in PPO, VO2peak, lactate threshold 1, and the anaerobic threshold for both groups (p < 0.05). Mean power output (MPO) obtained from time-trial was improved in C and C + E (p < 0.05). Isokinetic sprint test revealed increased PPO in both groups, whereas MPO was only changed in C (p < 0.05). Strength parameters were unaffected. Although metabolic stimuli and markers of muscle damage were higher in C + E compared to C, improvements of endurance performance and capacity were not significantly different between C and C + E. Conclusions: Despite a higher metabolic, respiratory, and muscular demand, chronic additional superimposed EMS during cycling does not result in superior improvements in endurance and strength performance compared to the traditional cycling.